2013
DOI: 10.1002/anie.201301516
|View full text |Cite
|
Sign up to set email alerts
|

An Azobenzene Unit Embedded in a Cyclopeptide as a Type‐Specific and Spatially Directed Switch

Abstract: By embedding an azobenzene unit into a chiral scaffold, switching of azobenzene from the trans-(P) isomer to the cis-(P) isomer and back was achieved (black arrows in picture). The embedding leads to a flipping process in which the phenyl rings can only move directly towards one another in the switching process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 53 publications
0
19
0
1
Order By: Relevance
“…The CD spectrum at PSS 435 represents an average between E and Z isomers CD spectra (cyan line). It has been reported that azobenzene could generate P or M helical chirality . We have firstly optimized the geometry of E ‐( P )‐ 1 , E ‐( M )‐ 1 , Z ‐( P )‐ 1 , and Z ‐( M )‐ 1 by using B3LYP/6‐311G functional and basis set (Figure and Figure S11 in the Supporting Information).…”
Section: Methodsmentioning
confidence: 99%
“…The CD spectrum at PSS 435 represents an average between E and Z isomers CD spectra (cyan line). It has been reported that azobenzene could generate P or M helical chirality . We have firstly optimized the geometry of E ‐( P )‐ 1 , E ‐( M )‐ 1 , Z ‐( P )‐ 1 , and Z ‐( M )‐ 1 by using B3LYP/6‐311G functional and basis set (Figure and Figure S11 in the Supporting Information).…”
Section: Methodsmentioning
confidence: 99%
“…This result is important because it also suggests that the trans → cis isomerization of the photoresponsive hinge may occur following an unidirectional motion, as it has been demonstrated by Haberhauer et al. in the case of azobenzenes clamped with small cyclo‐peptide scaffolds ,…”
Section: Resultsmentioning
confidence: 99%
“…Azobenzene and its derivatives can undergo reversible trans-cis isomerization upon irradiation with UV or visible light at certain wavelength [4][5][6]. Induced by the reversible change of molecular shape of azobenzene moiety, azopolymers demonstrate a variety of photoresponsive properties, and result in a number of practical applications, such as optical information storage [7,8], actuators [9,10], surface gratings [11][12][13], light-driven molecular switches [14,15], sustained-release drugs [16][17][18], light-controlled microfluidics and other photonic devices [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%